Enacting Instagram-mediated writing at an Islamic primary school: Indonesian case - Ali Basir; Misdi Misdi (La Tansa Mashiro, 2020)
In teaching and learning process, teacher needs strategy or media to make English learning active. Sometimes, high school students felt boring and they cannot relate to nor understand the material that is presented to them each day in class. To this, the varieties of strategy or media during teacher learning are needed to make them excited and motivated. Instagram, as one of the media, can be manipulated as education tool to the teacher and students. Employed descriptive research design, the enactment of instagram-mediated writing was employed to see students’ engagement in English writing. The findings show that writing activities go actively and students have positive responses.